Proposta de otimização do processo de obtenção de furos de pequenas dimensões em liga de titânio Ti-6Al-4V - Pereira, Murilo Sagrillo (2017)
Multi-objective optimization of multiple process characteristics, aiming at quality improvement, is necessary as it directly influences decision making, which is a determinant element for the satisfactory execution of a process. Mechanical manufacturing processes, more specifically machining, behave in the same way. Several multi-objective optimization techniques are provided by the literature, however, they generally do not consider the correlation structure between the multiple quality characteristics, as well as the different degrees of importance of them, resulting in the obtaining of inadequate optimal points. Thus, this study aims to propose an optimization of the process of obtaining small-dimension holes, in the Ti-6Al-4V titanium alloy by means of the method called the Weighted Multivariate Mean Square Error (EQMMP). The method is capable of generating uncorrelated weighted objective functions from the original responses by means of a weighting process that unifies Principal Component Analysis (ACP) and Response Surface Methodology (MSR). Initially, there will be a database tabulation available in the literature, related to a properly planned experiment of small dry holes in Ti-6Al-4V. The input parameters considered for this study are the feed rate (f), the spindle speed (N) and the air pressure (P) and, as quality characteristics were considered: the overcut (s), the conicity (con), the circularity error (circ) and the Thrust force (Ff). Next, the steps of the procedure for obtaining the EQMMP formulation are applied. By executing the Genetic Algorithm (GA) on it, in order to find the optimal process configurations. The optimum condition for the execution of small holes obtained by the method was the combination of a feed rate of 9.81mm / min, spindle speed of 5000 min-1 and 6 bar of air pressure. The results of optimization of quality characteristics were satisfactory and consistent with studies published in the area. It is expected that the results obtained in this study, allow to establish parameters of drilling processes that generate small-dimension holes of good quality, titanium alloy Ti-6Al-4V.